Pengaruh Manajemen Modal Kerja Terhadap Tingkat Profitabilitas Pada Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2010-2013 - Santhi, Istri Widya; Sutrisna Dewi, Sayu Ketut (E-Jurnal Manajemen; Vol 3 No 12 (2014), 2014)
The purpose of this study was to determine the effect of working capital management which consists of cash turnover, working capital turnover, inventory turnover and accounts receivable turnover to the level of profitability in the food and beverage companies listed in Indonesia Stock Exchange Period 2010-2013. This study used a quantitative research is to study and look at the financial statements of food and beverage companies listed in Indonesia Stock Exchange 2010-2013 and found a sample of 8 companies. The data analysis technique used is multiple linear regression. Obtained findings that working capital management which consists of cash turnover, working capital turnover, inventory turnover and accounts receivable turnover simultaneous effect on profitability in food and beverage companies listed in Indonesia Stock Exchange 2010-2013. Furthermore, it was found that the management of working capital consisting of cash turnover, working capital turnover, inventory turnover and accounts receivable turnover partial effect on profitability in food and beverage companies listed in Indonesia Stock Exchange 2010-2013.
Keywords: Perputaran Kas, Perputaran Modal Kerja, Perputaran Persediaan, Perputaran Piutang, Profitabilitas